CARDIOVASCULAR DISEASES: PREVENTION, CAUSES AND METHODS OF TREATMENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article considers the significance, etiology, clinical symptoms, diagnosis and treatment methods of cardiovascular diseases in the modern healthcare system. risk factors of diseases such as ischemic heart disease, myocardial infarction and hypertension, including modifiable and non-modifiable factors, are analyzed in detail. illuminates the role of atherosclerosis and pathophysiological processes in the development of cardiovascular diseases. the importance of laboratory tests used in the diagnosis of diseases is also emphasized. the article pays special attention to preventive measures, explains the importance of following a healthy lifestyle and controlling risk factors. The research shows the need for a comprehensive approach to effectively manage cardiovascular diseases.